The effect of Teach-back method education on the control of asthma and family care pressure of patients in Iran - Imanipour, Mohammad; Molazem, Zahra; Rakhshan, Mahnaz; Fallahi, Mohammad Javad; Sadaf, Amir Mohammad Atashin (Investigación y Educación en Enfermería, 2023)
Objective. To investigate the effect of teach-back education on patient asthma control and family care pressure of patients with asthma. Methods. The present study is a clinical trial and the study population was patients referred to Shahid Faghihi and Shahid Motahhari clinics in Shiraz, Iran. 58 patients with asthma and their caregivers were randomly assigned to the intervention and control groups, for a total of 29 subjects in each group. In the intervention group: the teach-back method was delivered individually to the patient and his or her primary caregiver in three sessions of approximately 60 minutes at one-day intervals. each session included presentations, practical techniques and a booklet. In this study, patients and caregivers in the control group were not trained. Before the intervention, 4 and 8 weeks after the intervention, asthma control test and spirometry test were performed to evaluate asthma control; Also, before the intervention and 8 weeks after the intervention, Zarit test was performed to evaluate the care burden. Results. The findings of repeated measures tests showed that, compared to the control group, the intervention group obtained a greater increase in the vital capacity index (p=0.028) and in the disease control score (p=0.001), as well as a reduction in the burden of care on family members (p<0.001). Conclusion. The present study showed that teaching asthma related topics to the patient and her caregiver along with the follow-up and supervision of the nurse improves the asthma control of the patient and also reduces the caregiver pressure.